Solid-phase extraction in malondialdehyde analysis - Suttnar, J; Cermák, J; Dyr, J E (Analytical biochemistry, 1997)
Malondialdehyde (MDA) has been widely used as an index of lipoperoxidation in biological and medical sciences as well as in the food industry. A solid-phase extraction (SPE) of the condensation product of the MDA with 2-thiobarbituric acid (TBA) was developed using LiChrolut C18ec, 200 mg (Merck, Darmstadt, Germany), as a SPE cartridge and methanol as an eluent for sample pretreatment before HPLC analysis. The samples of blood plasma, platelet concentrates, or erythrocyte membranes (ghosts) were deproteinized by acetonitrile in the presence of sodium hydroxide prior to the reaction with TBA. The reaction mixture was processed using SPE. The SPE extracts (800 microL of methanol) were put to dryness and after dissolution with 100 microliters of mobile phase, 50 microliters was analyzed by RP-HPLC with fluorescence detection (excitation at 514 nm, emission at 556 nm). The mean MDA concentration in plasmas of 32 healthy donors was 0.37 +/- 0.25 mumol/L and the mean MDA concentration in normal ghosts was 8.3 +/- 4.1 pmol/microgram of protein content. In the case of a patient with a severe form of beta-thalassemia, the concentration of plasma MDA was raised to 1.22 mumol/L and the amount of MDA in erythrocytal ghosts was raised to 21.05 pmol/microgram of protein content. MDA concentration in platelet concentrates (six bags) in the first day of storage was 0.46 +/- 0.18 mumol/L and in the fifth day of storage was 0.55 +/- 0.44 mumol/L.
Keywords: referenční hodnoty; methanol; Chromatography, Liquid; Humans; Malondialdehyde; proteiny; Proteins; Chemical Precipitation; trombocyty; peroxidace lipidů; Erythrocyte Membrane; Solvents; lidé; rozpouštědla; Blood Platelets; chromatografie kapalinová; erytrocytární membrána; thiobarbituráty; Thiobarbiturates; Methanol; Reference Values; chemická precipitace; malondialdehyd; Lipid Peroxidation